Testing of Kaempferia galanga extracts against cancer cell lines - Norhanom, A.W.; Ashril, Y.; Awang, K.; Hamid A. Hadi, A. (Malaysian Journal of Science, 1999)
. Extracts of Kaempferia galanga, from the Zingerberaceae family, were screened for anti-tumour promoting and anti-tumour activities. The bioassay involved the inhibition of 12-0-tetradecanoylphorbolÂ13-acetate induced Epstein-Barr virus early antigen activation in Raji cells. KB cells were used for the anti-tumour screening. Chloroform extracts showed strong anti-tumour promoting activity against Raji cells (ED50 38 .ig mL-1) and anti-tumour activity against KB cells (ED50 7.6 Âµg mL-1). Petroleum ether extracts were active against the KB cells (ED50 8.2 ug/mL) but the methanol extracts was not active